(3TQM GdeLSWis - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s
(3ChdgG (B:s
(3JHOC HGKfGA GdaUd GdPi bHd GdaUd ajeG jMJGL Cf jJbOe ajYde ai JHjf CeQ SGFO GdchGcH s
(3BNQgG (B:s
(3YOO GdRjGOI hGdfbUGf ai GdWhd HSHH GdEfMQGa Je GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B194s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi s
Keywords: (3Gdadcs